Fungus mediated synthesis of biomedically important cerium oxide nanoparticles - Khan, Shadab Ali; Ahmad, Absar (Materials Research Bulletin, 2013)
Nanomaterials can be synthesized by chemical, physical and the more recently discovered biological routes. The biological routes are advantageous over the chemical and physical ones as unlike these, the biological synthesis protocols occur at ambient conditions, are cheap, non-toxic and eco-friendly. Although purely biological and bioinspired methods for the synthesis of nanomaterials are environmentally benign and energy conserving processes, their true potential has not been explored yet and attempts are being made to extend the formation of technologically important nanoparticles using microorganisms like fungi. Though there have been reports on the biosynthesis of oxide nanoparticles by our group in the past, no attempts have been made to employ fungi for the synthesis of nanoparticles of rare earth metals or lanthanides. Here we report for the first time, the bin-inspired synthesis of biomedically important cerium oxide (CeO2) nanoparticles using the thermophilic fungus Humicola sp. The fungus Humicola sp. when exposed to aqueous solutions of oxide precursor cerium (III) nitrate hexahydrate (CeN3O9 center dot 6H(2)O) results in the extracellular formation of CeO2 nanoparticles containing Ce (III) and Ce (IV) mixed oxidation states, confirmed by X-ray Photoemission Spectroscopy (XPS). The formed nanoparticles are naturally capped by proteins secreted by the fungus and thus do not agglomerate, are highly stable, water dispersible and are highly fluorescent as well. The biosynthesized nanoparticles were characterized by UV-vis spectroscopy, Photoluminescence spectroscopy (PL), Transmission Electron Microscopy (TEM), Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and X-ray Photoemission Spectroscopy (XPS). (c) 2013 Elsevier Ltd. All rights reserved.
Keywords: Electron microscopy; Nanostuctures; Optical properties; Oxides; X-ray diffraction

Phase, size and shape transformation by fungal biotransformation of bulk TiO2 - Khan, Shadab Ali; Ahmad, Absar (Chemical Engineering Journal, 2013)
Nanosynthesis is an ever expanding frontier in recent years in view of its implications to many future technologies covering diverse fields. Considerable progress has been made realizing high quality synthesis of elemental nanomaterials as well as compounds as chemical, biological and physical routes. The issue of technologically viable large scale synthesis still continues to be a challenge. Here we demonstrate a novel environmentally friendly top down approach to nanosynthesis which exploits the strength and peculiarities of fungus based bioleaching in extracting radicals from compounds and then providing them with a reactive as well as capping environment. Thus protein capped nanoparticles of TiO2 (5-28 nm, circular and brookite phase) are formed directly from micron size (150-250 nm, disc shape, anatase phase) powder by exposing them to a medium of fungus Humicola sp. at just 50 degrees C. The fungus Humicola sp. is not only useful for the synthesis of nanoparticles but also for the transformation of shape, phase and size of TiO2. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Anatase; Biotransformation; Brookite; humicola sp; TiO2

Enzyme mediated synthesis of water-dispersible, naturally protein capped, monodispersed gold nanoparticles; their characterization and mechanistic aspects - Khan, Shadab Ali; Ahmad, Absar (RSC Advances, 2014)
Inorganic nanomaterials are conventionally synthesized under harsh environments like extremes of temperature, pressure and pH. These methods are eco-unfriendly, expensive, toxic, cumbersome, yield bigger particles which agglomerate due to not being capped by capping agents. In contrast, biological synthesis of inorganic nanomaterials occurs under ambient conditions viz. room temperature, atmospheric pressure, physiological pH and is reliable, eco-friendly and cheap. We have already reported the extracellular biosynthesis of monodispersed gold nanoparticles from the whole cells of novel extremophilic actinomycete Thermomonospora sp. In order to know the exact mechanism of synthesis, we decided to investigating it further. Here we describe the simple protocol for purification of the temperature and SDS resistant sulfite reductase enzyme and organic capping molecule, which are required for the synthesis and stabilization of gold nanoparticles respectively. This purified enzyme was then employed for the synthesis of gold nanoparticles along with the capping molecule, which render gold nanoparticles monodispersed in solution.

Extracellular biosynthesis of gadolinium oxide (Gd2O3) nanoparticles, their biodistribution and bioconjugation with the chemically modified anticancer drug taxol - Khan, Shadab Ali; Gambhir, Sanjay; Ahmad, Absar (Beilstein Journal of Nanotechnology, 2014)
As a part of our programme to develop nanobioconjugates for the treatment of cancer, we first synthesized extracellular, protein-capped, highly stable and well-dispersed gadolinium oxide (Gd2O3) nanoparticles by using thermophilic fungus Humicola sp. The biodistribution of the nanoparticles in rats was checked by radiolabelling with Tc-99m. Finally, these nanoparticles were bioconjugated with the chemically modified anticancer drug taxol with the aim of characterizing the role of this bioconjugate in the treatment of cancer. The biosynthesized Gd2O3 nanoparticles were characterized by UV-vis spectroscopy, transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoemission spectroscopy (XPS). The Gd2O3-taxol bioconjugate was confirmed by UV-vis spectroscopy and fluorescence microscopy and was purified by using high performance liquid chromatography (HPLC).
Keywords: bioconjugation; biodistribution; gadolinium oxide; humicola sp; transmission electron microscopy

Fungus-mediated preferential bioleaching of waste material such as fly - ash as a means of producing extracellular, protein capped, fluorescent and water soluble silica nanoparticles - Khan, Shadab Ali; Uddin, Imran; Moeez, Sana; Ahmad, Absar (PLoS One, 2014)
In this paper, we for the first time show the ability of the mesophilic fungus Fusarium oxysporum in the bioleaching of waste material such as Fly-ash for the extracellular production of highly crystalline and highly stable, protein capped, fluorescent and water soluble silica nanoparticles at ambient conditions. When the fungus Fusarium oxysporum is exposed to Fly-ash, it is capable of selectively leaching out silica nanoparticles of quasi-spherical morphology within 24 h of reaction. These silica nanoparticles have been completely characterized by UV-vis spectroscopy, Photoluminescence (PL), Transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Energy dispersive analysis of Xrays (EDAX).

Ovalbumin-mediated synthesis and simultaneous functionalization of graphene with increased protein stability - Ullah, Riaz; Khan, Shadab Ali; Aladresi, Aref Ali Mohammed; Alharbi, Sulaiman Ali; Chinnathambi, Arunachalam (Green Chemistry Letters and Reviews, 2020)
In this article, we have shown an easy, one-step, protein-directed approach for the synthesis of water-soluble and functional graphene using ovalbumin. The obtained ovalbumin functionalized graphene was characterized by UV-visible spectroscopy, X-ray diffraction, Raman spectroscopy, and Fourier transform infrared spectroscopy. Atomic force microscopy was used to check the attachment/functionalization of ovalbumin on grapheme sheets. It was shown that the functionalization of ovalbumin on grapheme sheets makes the protein more thermally stable compare to free ovalbumin, which has been shown by using sodium dodecyl sulfate polyacrylamide gel electrophoresis.
Keywords: Atomic force microscopy; graphene; graphene oxide; Ovalbumin; SDS-PAGE; thermal degradation